2023
DOI: 10.1371/journal.pone.0277213
|View full text |Cite
|
Sign up to set email alerts
|

The effect of synbiotic supplementation on hypothyroidism: A randomized double-blind placebo controlled clinical trial

Abstract: Objective We hypothesize that synbiotic supplementation could modulate the intestinal microbiota and subsequently, improve the condition of hypothyroid patients. Methods Fifty-six adult hypothyroid patients were recruited to this double-blind, placebo-controlled, randomized clinical trial. The intervention was 10 weeks of synbiotic (500 mg of 109 CFU/g probiotics plus fructo-oligosaccharide, n = 28) compared to placebo (lactose, magnesium stearate, talc, and silicon dioxide, n = 28). Randomization and alloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Majid Ramezani et al, who studied the effect of synbiotics on the course of hypothyroidism, reported an improvement in the quality of life of patients despite the lack of effect of supplementation with a product containing post-biotic bacteria on the concentration of TSH in plasma. Therefore, the supply of probiotic bacteria through the consumption of fermented products is recommended [46].…”
Section: Discussionmentioning
confidence: 99%
“…Majid Ramezani et al, who studied the effect of synbiotics on the course of hypothyroidism, reported an improvement in the quality of life of patients despite the lack of effect of supplementation with a product containing post-biotic bacteria on the concentration of TSH in plasma. Therefore, the supply of probiotic bacteria through the consumption of fermented products is recommended [46].…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies observed a significant positive (but minimal clinical) effect of synbiotic supplementation on serum thyroid markers in patients with hypothyroidism using LT4 compared with their placebo-treated counterparts. Unfortunately, both studies lacked information on gut microbiota composition and functionality before and after the intervention 34 35. The present IMITHOT study is the first to test the effect of restoring intestinal homeostasis with healthy microbiota using faecal microbiota transplantations (FMTs) on thyroid function in medication-naïve patients with subclinical autoimmune hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…This blend showed no significant effect on anti-TPO [31]. Another study examined the effects of a synbiotic (500 mg of 10 9 CFU/g probiotics plus fructooligosaccharide) on adult hypothyroid patients [32]. Although a 10-week supplementation had no beneficial effects on serum thyroid-stimulating hormones, it did result in improved blood pressure and quality of life among patients with hypothyroidism [32].…”
Section: Introductionmentioning
confidence: 99%
“…Another study examined the effects of a synbiotic (500 mg of 10 9 CFU/g probiotics plus fructooligosaccharide) on adult hypothyroid patients [32]. Although a 10-week supplementation had no beneficial effects on serum thyroid-stimulating hormones, it did result in improved blood pressure and quality of life among patients with hypothyroidism [32]. Hashimoto's thyroiditis is characterized by an increased inflammatory burden, accompanied by increased red cell distribution width.…”
Section: Introductionmentioning
confidence: 99%